Differential Impacts of Land Use and Precipitation on "Ecosystem Water Yield". Issue 8 (16th August 2018) - Rohatyn, Shani; Rotenberg, Eyal; Ramati, Efrat; Tatarinov, Fyodor; Tas, Eran; Yakir, Dan
Abstract: Ecosystem evapotranspiration (ET) can approach annual precipitation (P) often leaving a residual [P‐ET], referred to as an ecosystem water yield (WYe). Using a mobile lab, we estimate ET and WYe, in paired forest and nonforest (shrub or grassland) sites along the precipitation gradient (285–755 mm a −1 ) in Israel. WYe was 69 mm in the dry sites and was further reduced by ∼51 mm by forestation. Both WYe and the impact of forestation increased in the wetter sites, with forestation reducing WYe by >200 mm, equivalent to ∼30% of the local P. This was associated with increase in ET by a factor of 2.2 and 1.8 in the forest and nonforest sites, respectively, along the rainfall gradient. Losses in WYe due to forestation approached a maximum of ∼200 mm above P ∼ 500 mm, but the forest WYe could vary between ∼300 mm at P = 900 mm and ∼100 mm at P = 500 mm (with equivalent change in WYe between 500 and 300 mm in the nonforest sites), reflecting the increasing "hydrological cost" associated with vegetation ET and the expected climate change in these regions. The results quantify the interactions of land use and climate on ecosystem ET, indicating that in dry climates, afforestation impact on WYe varies significantly across small spatial scales and can reduce WYe with significant impacts on local hydrology. Such impact may be diminished by management (e.g., plant species, thinning, and grazing) but should also consider the trade‐offs with other ecosystem services (e.g., carbon sequestration, soil protection, and surface cooling). Key Points: In dry climate ecosystem, evapotranspiration approaches precipitation with small residual "ecosystem water yield" Along a rainfall gradient of 285–755 mm, forestation can reduces ecosystem water yield by >200 mm, equivalent to ∼30% of the local rainfall At the wet sites, ET is near constant with water yields reflecting changes in P and the increasing hydrological cost of forestation